The telomeric sequence is directly attached to the HRS60 subtelomeric tandem repeat in tobacco chromosomes - Fajkus, J; Královics, R; Kovarík, A; Fajkusová, L (FEBS letters, 1995)
PCR and primers derived from the telomeric repeat (CCCTAAA)n and from the tobacco subtelomeric tandemly repetitive sequence HRS60 (EMBL X12489) were used to amplify the region linking the two loci. A 131 bp PCR product was obtained both from total tobacco DNA and from the DNA fraction enriched for telomeres. Its sequence only consists of the telomeric primer and the attached region of the HRS60 repetitive unit up to the end of the sequence complementary to the HRS60 primer. The site of direct continuity between the two sequences is formed by a (dA)7 tract.
Keywords: Sequence Analysis, DNA; Plants, Toxic; telomery; satelitní DNA; Base Sequence; Nicotiana; Molecular Sequence Data; DNA, Satellite; Repetitive Sequences, Nucleic Acid; molekulární sekvence - údaje; sekvenční analýza DNA; Telomere; jedovaté rostliny; tabák; polymerázová řetězová reakce; Polymerase Chain Reaction; repetitivní sekvence nukleových kyselin; sekvence nukleotidů